Pengembangan WEB Comic Fantasi Cerita Sura dan Baya untuk Mengurangi Tindakan Rasisme Remaja Kota Surabaya - Nasrullah, Yusuf; Sumarwahyudi, Sumarwahyudi; Prasetyo, Abdul Rahman (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
One negative impact in teenage friendship is the appearance of racial motive bullying. As we know, Indonesia is a country with thousands of cultures. Likewise in Surabaya, it was recorded several times that this activity happened in the middle of the beautiful teenage friendship. Therefore, a developed product formed as a fantasy web comic which is published in an online publisher and not be printed entitled